AN ANALYSIS OF THE MAIN CHARACTER IN THE MOVIE "SOUTHPAW" BY ANTOINE FUQUA - Dwi; Kurniawan, catur (Lingustic, Literature and English Education, 2023)
Movies are identical to characters. If the characters in a film are less interesting in terms of storyline, then the audience's interest will also decrease. Therefore it is important to have a character that describes the character's personality. The film SouthPaw (2015) features the main character with the theme of boxing sports with a character who loves his family and has to lose his beloved wife. This study aims to analyze a movie from the SouthPaw film about the personality of the main character, Billy Hope. The data used in this study is from the film itself which can be watched on the HBO application or other free official sites by telling the life of a boxer who has a dark life story. This research was analyzed using descriptive qualitative methods. This research shows how the personality of Billy Hope, the main character played by Jake Gyllenhaal,